Vulvar intraepithelial neoplasia and microinvasive carcinoma of the vulva. Issue 11 (November 1984) - Buckley, C H; Butler, E B; Fox, H
Abstract : The pathological, cytological, and clinical features of vulvar intraepithelial neoplasia (VIN) are described. The rate of progression of VIN III to an invasive carcinoma is very low and spontaneous regression can occur. These features prevent the drawing of a direct analogy between vulvar and cervical intraepithelial neoplasia. The concept of microinvasive carcinoma of the vulva is discussed, and it is concluded that no satisfactory definition of this entity has been achieved.